The Role of the Job Creation Law Policy in Overcoming Indonesia’s Middle Income Trap: Analysis of the Effects of FDI, HDI, and Minimum Wages on the Open Unemployment Rate - Yosephin Suci Wulandari; Nely Aida; Arivina Ratih Taher (Revenue Journal: Management and Entrepreneurship, 2026)
This study analyzes the effect of Foreign Direct Investment (FDI), Human Development Index (HDI), and Regional Minimum Wage (RMW) on the Open Unemployment Rate (OUR) in Indonesia within the context of the implementation of the Job Creation Law policy. The study aims to examine the role of these variables in supporting Indonesia’s efforts to overcome the Middle-Income Trap. This research employs a quantitative descriptive approach using secondary time series data covering the period 1990–2024. The analysis method applied is the Autoregressive Distributed Lag (ARDL) model to identify both short-run and long-run relationships among variables. The results indicate that FDI has a significant effect on the Open Unemployment Rate in both the short run and long run. In the short run, FDI initially reduces unemployment; however, its lagged effects show a temporary increase in unemployment due to labor market adjustments and the capital-intensive nature of foreign investment. In the long run, FDI significantly reduces unemployment through industrial expansion, productivity growth, and employment creation. Meanwhile, the Human Development Index has a negative but statistically insignificant effect on unemployment, indicating that improvements in human development have not yet been fully aligned with labor market demands. The Regional Minimum Wage also shows a positive but insignificant effect on unemployment, suggesting that wage increases are not the primary determinant of unemployment in Indonesia. Furthermore, the Error Correction Term (ECT) confirms the existence of a long-run equilibrium relationship with a relatively rapid adjustment process. Overall, the findings suggest that productive investment, labor market reforms, and improvements in human capital quality are essential to reducing unemployment and supporting Indonesia’s transition toward a high-income economy.